Smart Multiplug: IoT-Based Energy Monitoring and Remote-Control System for Sustainable Power Management - Bajracharya, Samyak; Paudel, Sukriti; Lama, Pratibha; Upadhyay, Rishikesh (International Journal on Engineering Technology, 2025)
This paper presents an IoT-based smart multiplug system designed for energy conservation and device protection. The system leverages an ESP32 microcontroller with integrated Wi-Fi connectivity to enable remote monitoring and control of electrical appliances through the Arduino IoT Cloud platform. Key features include real-time current and temperature monitoring, remote switching capability, and customizable threshold alerts for device protection. Evaluation results demonstrate the system’s effectiveness in monitoring power consumption with a current threshold of 10A and temperature threshold of 70°C for safety. The total implementation cost of approximately 25 makes it an economically viable alternative to commercial solutions. The proposed system successfully addresses the limitations of traditional electrical outlets by providing seamless integration of monitoring and control capabilities, thereby enhancing energy efficiency and device protection in both residential and commercial settings.